(untitled) (International Journal of Engineering and Computer Science, 2013)
The use of cache memories are so persistent in today’s computer systems it is difficult to imagine processors without them. Cache memories, along with virtual memories and processor registers form a field of memory hierarchies that rely on the principle of locality of reference. Most applications exhibit temporal and spatial localities among instructions and data. Spatial locality implies that memory locations that are spatially near the currently referenced address will likely be referenced. Temporal locality implies that the currently referenced address will likely be referenced in the near future. Memory hierarchies are intended to keep most likely referenced items in the fastest devices. This results in an effective reduction in access time.